Seabird and reef conservation must include coral islands. (June 2023) - Berr, Tristan; Dias, Maria P.; Andréfouët, Serge; Davies, Tammy; Handley, Jonathan; Le Corre, Matthieu; Millon, Alexandre; Vidal, Éric
Abstract: Tropical seabirds exert key roles in reef ecosystems but face growing threats from climate change, especially on coral reef islands (CRIs). Therefore, we advocate for a more comprehensive, global data exchange on CRIs and CRI-dependent seabirds and outline steps for improving their study and conservation.